2006
DOI: 10.1073/pnas.0606512103
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant vaccinia/fowlpox NY-ESO-1 vaccines induce both humoral and cellular NY-ESO-1-specific immune responses in cancer patients

Abstract: NY-ESO-1 is a cancer͞testis antigen expressed in a range of human malignancies, and a number of vaccine strategies targeting NY-ESO-1 are being developed. In the present study, the safety and immunogenicity of recombinant vaccinia-NY-ESO-1 and recombinant fowlpox-NY-ESO-1 were analyzed in a series of 36 patients with a range of different tumor types. Each construct was first tested individually at two different dose levels and then in a prime-boost setting with recombinant vaccinia-NY-ESO-1 followed by recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
148
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(154 citation statements)
references
References 26 publications
1
148
0
5
Order By: Relevance
“…Moreover, there is compelling evidence demonstrating in both animals and humans that tumors are able to provoke adaptive anti-tumor immune responses mediated by B cells and CD4+ and CD8+ T cells and to initiate innate immune responses mediated by NK or NKT cells [6][7][8][9][10][11][12]. For example, the tumor-associated antigens NY-ESO-1 and LAGE-1 have been shown to be expressed on epithelial ovarian cancers and have been used in tumor vaccines to induce both anti-tumor antibody and tumor-specific CD4+ and CD8+ T cell responses in patients with ovarian cancer [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is compelling evidence demonstrating in both animals and humans that tumors are able to provoke adaptive anti-tumor immune responses mediated by B cells and CD4+ and CD8+ T cells and to initiate innate immune responses mediated by NK or NKT cells [6][7][8][9][10][11][12]. For example, the tumor-associated antigens NY-ESO-1 and LAGE-1 have been shown to be expressed on epithelial ovarian cancers and have been used in tumor vaccines to induce both anti-tumor antibody and tumor-specific CD4+ and CD8+ T cell responses in patients with ovarian cancer [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This combination of restricted normal tissue expression, spontaneous immunogenicity and frequent tumor expression has pushed MAGE and NY-ESO-1 to the forefront of tumor immunotherapy as attractive targets for cancer vaccines, 1,8 and multiple clinical trials using these 2 antigens have been carried out, with promising results observed in some studies. [9][10][11][12][13][14][15][16][17] Following the initial identification of MAGE and NY-ESO-1 families, more than 80 gene or gene families have been described as CT or CT candidate genes in the literature. These genes have been organized and annotated into a CT database by the Ludwig Institute for Cancer Research (http://www.cancerimmunity.org/ Ctdatabase/ and http://www.cta.lncc.br).…”
mentioning
confidence: 99%
“…Essentially similar findings were obtained by studies using other preparations of NY-ESO-1 protein vaccine. 11,12,15 …”
mentioning
confidence: 99%
“…of the antigen with various adjuvants. [6][7][8][9][10][11][12][13][14] These studies established the safety of the NY-ESO-1 vaccine and demonstrated its immunogenicity.…”
mentioning
confidence: 99%
See 1 more Smart Citation